2021
DOI: 10.1027/2698-1866/a000013
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Perceptual Speed Between Educational Contexts

Abstract: Abstract. Perceptual speed is a basic component of cognitive functioning that allows people to efficiently process novel visual stimuli and quickly react to them. In educational studies, tests measuring perceptual speed are frequently developed using students from regular schools without considering students with special educational needs. Therefore, it is unclear whether these instruments allow valid comparisons between different school tracks. The present study on N = 3,312 students from the National Educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Perceptual speed denotes the ability to quickly and accurately identify similarities and differences between sets of visual stimuli ( Gnambs et al, 2021 ; Schaie, 1989 ). No study has examined perceptual speed in middle-to-old aged autistic adults in the current literature.…”
Section: Resultsmentioning
confidence: 99%
“…Perceptual speed denotes the ability to quickly and accurately identify similarities and differences between sets of visual stimuli ( Gnambs et al, 2021 ; Schaie, 1989 ). No study has examined perceptual speed in middle-to-old aged autistic adults in the current literature.…”
Section: Resultsmentioning
confidence: 99%
“…Student attitudes and experiences in virtual music education have been the subject of extensive research, with a focus on factors such as psychological needs satisfaction, engagement, and satisfaction with online learning (Wong, 2022). Gnambs et al (2021) found a strong connection between the satisfaction of psychological needs and students' behaviour in the educational context highlighting the importance of students' perceptions of empowerment, usefulness, success, interest, and caring in relation to their engagement in the class in virtual music education (Kelley, 2020). Additionally, Sakata (2022) conducted a qualitative case study that examined the effect of learner-centred pedagogy on student engagement in a virtual elementary instrumental music programme.…”
Section: Student Attitudes and Experiences In Virtual Music Educationmentioning
confidence: 99%
“…Categorical data are generated by items that are answered using ordered categories, such as in dichotomous indicators (e.g., items in ability tests are scored as 0 [ incorrect ] and 1 [ correct ]; e.g., Gnambs et al, 2021) and rating scales containing 3 to k response options, with anchors such as 1 ( strongly disagree ) and k ( strongly agree ; e.g., Dierickx et al, 2020). Many assessment instruments in psychology and neighboring sciences generate this type of discrete data (Simms et al, 2019).…”
Section: Estimating the Cfa Model On The Basis Of Continuous And Disc...mentioning
confidence: 99%